Cases in online interview research - Salmons, Janet (SAGE, 2012)
In an era of constrained research budgets, online interviewing opens up immense possibilities: A researcher can literally conduct a global study without ever leaving home. But more than a decade after these technologies started to become available, there are still few studies on how to utilize online interviews in research. This book provides 10 cases of research conducted using online interviews, with data collected through text-based, videoconferencing, multichannel meeting, and immersive 3-D environments. Each case is followed by two commentaries: one from another expert contributor, the second from Janet Salmons as editor. A open-access companion website at www.sagepub.com/salmons provides sample syllabi, assignment ideas, links to other work by the book's contributors, and guidelines for utilizing the book's E-Interview Research Framework.